Development and validation of sequential sampling plans for Caliothrips phaseoli (Thysanoptera: Thripidae) on soybean - Perotti, Evangelina (2026)
The american bean thrips (ABT), Caliothrips phaseoli (Hood), is a serious pest of soybeans in South America. Both research and management require reliable sampling protocols, thus the objectives were to (1) to determine the spatial dispersion of ABT in soybean fields, (2) develop sequential sampling plans (SSP) and (3) evaluate their performance. Taylor Power Law (TPL) and Iwao Patchiness Regression (IPR) models provided very good fit with slopes significantly higher than 1, suggesting an aggregated distribution pattern of ABT in soybean fields over a five-year field study. Green’s fixed-precision SSP (based on TPL) yielded smaller expected average sample number than did Kuno’s fixed-precision SSP (based on IPR) for the same precision level. Although this suggests that Green´s model is more efficient because it demands less sampling effort for the same precision level, validation by resampling of independent datasets shows that at least for low ABT densities the real precision achieved with Kuno’s protocol is higher than expected. Recalculating SSPs so that they yield, on average, the desired precision allowed their comparison over the same real precision. The advantage of one SSP over the other depended on ABT density. For users willing to make highly precise density estimations, the protocol choice is not clearcut. However, for other users unable to invest the time and effort to obtain such precision, Kuno’s protocol may be more efficient.